“El baile de los diablitos“ en Boruca: Magia vs Dominación - Castro Incera, Denis (2016)
This paper presents a description and interpretation of “The dance of the devils“ in Boruca is performed. Ritual year after year allows revitalize local traditions in a celebration of resistance and survival.